Remote Sensing Study on Interlinking of rivers from Pennar to Cauvery - Rajesh, SVJSS; Rao, BSP; Niranjan, K (International Journal of Computer Sciences and Engineering, 2025)
Water scarcity is becoming a grave problem in India due to monsoon effect and increasing population. More over the rainfall in the country is also unevenly distributed. As a result the regions receiving heavy precipitation are facing floods resulting in huge amount of water runs into the sea at the same time lack of rain fall regions are suffering with droughts and famines. To overcome the problems in the distribution of water, National Water Development Agency (NWDA) put a proposal of water transfer from surplus region to deficit regions. The total length of the present study is 483km. between Pennar (somasila) and Cauvery (Grand Anicut) and it consists of 10 km. buffer on both sides of the canal and it covers 17,215.68 sq. km. out of which area of 10,105.96 sq.km.is the proposed command area falling in Chittoor, Chengalpattu, North Arcott and South Arcott districts. The characteristics of the rocks, lineaments, drainage, settlements and land use/land cover are demarcated using IRS-P6, LISS-III data for better analysis. The study reveals that Current fallow land of 5340.14 km2 and 6307.98 km2 of cropland will be benefited for cultivation which is more than what NWDA estimated. The canal will provide water for irrigation and drinking to 4597 villages and 244 villages to be reclocated. 119 culverts and 24 aqueducts have to be constructed across the canal.